Religion and the Legal Institutional Combat against Corruption in Nigeria - Sibani, Clifford Meesua; Clifford-Sibani, Blessing Leera (NIU Journal of Social Sciences; Vol 10 No 1 (2024): NIU Journal of Social Sciences, Vol. 10 No. 1, March 2024DO - 10.58709/niujss.v10i1.1808, 2024)
Religion is man’s belief in the super abundant reality that controls the cosmic environs, propels humans’ worship and demand appeasement for pardon and favour. Corruption is the act of corrupting or the state of being corrupt, moral perversion; depravity, and perversion of integrity. The battle between religion and corruption in Nigeria is a moral one and calls for sanity and renewing of the mind. It has eaten deep into the fabrics of the nation with adverse effect on the poor masses. The perpetrating actors of corruption are found in all sectors of our nation but copiously amongst the elite and those in leadership. The objective of this research is to view the place of religious and legal institutions in combating corruptions in Nigerian. This research utilized historical approach as well as books, journals; internet materials etc as sources.  It was able to examine corruption in Nigeria, holistic definition of corruption, nature and characteristics of corruption, evil of corruption, and the causes of corruption, legal and institutional fight against corruption in Nigeria, how religion aids corruption and the role of religion in combating corruption as a social responsibility/intervention in Nigeria. It recommends that religious institution should as a matter of urgency be the watchdog and the conscience of the common man in nation with respect to combating corruption in Nigeria. Keywords: Religion, Legal, Institutional, corruption, Combat, Nigeria.